LncRNAs and epigenetic regulation of vascular endothelium: genome positioning system and regulators of chromatin modifiers. (April 2019) - Man, Hon-Sum Jeffrey; Marsden, Philip A
Highlights: Nuclear-enriched lncRNAs are important factors in endothelial cell biology. Nuclear-enriched lncRNAs have various mechanisms of action in endothelial cells. Conservation and knockout strategies are challenges for lncRNA models in vivo. Abstract : Epigenetic mechanisms regulate the cell type-specific expression of endothelial-enriched genes. A major question has been how chromatin modifiers without inherent sequence specificity can be targeted to genomic coordinates. Recently, long noncoding RNAs (lncRNAs) have emerged as candidates for specifying genomic positioning for chromatin modifiers. However, lncRNAs function by a number of mechanisms in both the nucleus and the cytoplasm. Recent studies indicate the existence of endothelial-enriched lncRNAs. This review discusses lncRNA regulation in endothelial cells with a focus on four recently described nuclear-enriched lncRNAs: MANTIS, LEENE, STEEL, and GATA6-AS. This emerging work on these lncRNAs contributes to our understanding of epigenetic regulation in the vascular endothelium with links to important themes in endothelial biology, including angiogenesis and shear stress.